MANAJEMEN PEMBINAAN KESISWAAN DALAM MENINGKATKAN KEIMANAN, KETAQWAAN DAN KARAKTER MULIA DI PESANTREN RAUDLATUL HASANAH - Sopian Sinaga (Jurnal Al-Fatih, 2018)
The construction of the student/students in increasing faith, devotion and noble character is very important given to learners to achieve the vision of the education of the nation makes the younger generation into the golden generation the hope of the nation. Boarding schools that are rising and got a good reception from the community of North Sumatra one is boarding Raudlatul Hasanah terrain. Researchers interested in researching and knowing the model of planning, implementation and supervision of student mentoring programme in order to increase faith, devotion and noble character santri. Researchers in collecting data method had been completed the interview, observation and document studies field. The result is one Hasanah Islamic boarding school Raudlatul best boarding school in Northern Sumatra have been doing various methods in order to coaching students in boarding schools.Among the methods and work done are conditioning methods, methods of coercion and kept students with positive activities, the provision of a conducive environment for the students, giving the example of the nanny, optimize wearing a sticker and writings that contain the motivation to live, and the existence of reward as well as a punishmen. Boarding school management in terms of supervision of students has been optimizing cooperation between students and ustadz pesantren. Students through the Organization of boarding and OPRH (Organization of the Pesantren Raudlatul Hasanah), while under the leadership of ustadz head of Parenting that includes 4 sections.